Factors Affecting the Number of Tourist Arrivals as Well as Unemployment and Poverty on Jambi's Economic Growth - Ary Dean Amry; Fidyah Safitri; Andini Destri Aulia; Kiki Nur Misriyah; Dendy Nurrokhim; Rian Hidayat (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
Tourism and economic growth are connected in various ways, where tourism can contribute to regional economic development. The benefits of the tourism sector in economic growth are the creation of jobs for local people. This study aims to determine the factors that affect the number of foreign and domestic tourist visits (X1), unemployment (X2) and poverty (X3) to Jambi's economic growth (Y). The method used in this quantitative research was conducted with the time series 2012-2022 and the data source used was secondary data. From the data collected, the results of this study indicate that the number of tourists, poverty, and unemployment have an effect but are not significant on economic growth in Jambi Province